The Applicability of Oxidative Stress Biomarkers in Assessing Chromium Induced Toxicity in the Fish Labeo rohita. (14th September 2014) - Kumari, Kanchan; Khare, Ankur; Dange, Swati
Abstract : The evaluation of metal's toxicity in freshwater is one of the imperative areas of research and there is an emergent concern on the development of techniques for detecting toxic effects in aquatic animals. Oxidative stress biomarkers are very useful in assessing the health of aquatic life and more in depth studies are necessary to establish an exact cause effect relationship. Therefore, to study the effectiveness of this approach, a laboratory study was conducted in the fish Labeo rohita as a function of hexavalent chromium and the toxicity indices using a battery of oxidative stress biomarkers such as catalase (CAT), superoxide dismutase (SOD), and glutathione reductase (GR) in the liver, muscle, gills, and brain have been studied along with biometric parameters, behavioral changes, and Cr bioaccumulation. A significant increased HSI was observed in contrast to CF which reduced significantly. SOD, CAT, and GR activity increased significantly in all the tissues of treated fishes. The bioaccumulation of Cr was highest in liver followed by gills, muscle, and brain. This study highlights the significance of using a set of integrated biomarker and advocate to include these parameters in National Water Quality Monitoring Program in areas potentially polluted with metals to assess the health of the ecosystem.